Desenvolvimento de uma base geoquímica regional para metais traço em sedimentos superficiais da bacia hidrográfica do rio Sergipe - Silva, Aldair Ferreira (2012)
The Sergipe River Basin is one of the most important basins of the State of Sergipe. It drains 16.7% of the total area of the State and has a resident population of 56.6% of the total population, shared by 26 cities. The aim of this project is to determine and assess the distribution and toxicity of trace metals Co, Cr, Cu, Ni, Mn, Pb and Zn in surface sediments of the Sergipe River Basin. It was collected nineteen sediment samples in December 2010. The extraction methods used were efficient, with good agreement, without significant difference and a confidence level of 95%. The total concentration of metals from the surface sediments showed a wide variation of values. The strong correlations among iron, manganese and other trace metals indicate that iron and manganese in inorganic major carriers control the distribution of metals in sediments of the study area. The total concentration of the determined metals was normalized from iron. The P1 site showed enriched by Ni and Pb, Cr by the site P5, P2 and P6 sites by Co and Cu site by P13. The enrichment factor (EF = 3.45) and index geoaccumulation (Igeo = 1.20) indicated contamination only in the site P13. According to the geochemical normalization, the Enrichment factor and index of geoaccumulation, the concentrations of metals from sediment analyzed can be seen from natural sources, except for the sites P1, P5 and P13, and the lines of regression can be used to define the basis of regional geochemistry (BGR). The application of PCA and HCA or geochemical suggests characteristic mechanism similar to the enrichment sites P1-P3, P6, P9-P10 (Group I) and sites P4-P5, P7, P8, P11-P19 (Group II). The site P1-P3 and P9 showed higher concentration at least of one value of TEL and / or TEC for Cu and Ni. According to the ratio of potential adverse impact of sediment to biota, QPEL-SQA and SQA-QPEC the examined samples, in general, are not affected, except for sites P1-P3, P9, P10 and P13 (moderately impacted).